The impact of the global budget system on dynamics of dental manpower and utilization of dental services - Laura Yueh-Guey Huang; Boyen Huang (Wolters Kluwer Medknow Publications, 2016)
Background: This study aimed to investigate dentists' supply and practice patterns following the implementation of the global budget system in Taiwan. Materials and Methods: Data of reimbursement claims, municipal socioeconomic status and dental manpower were collected from the National Health Insurance administration, the Ministry of Internal Affair, and the Ministry of Health and Welfare, respectively. A multivariate linear regression method was used for data analysis. Results: A municipality that reported a higher percentage of tertiary educated population (t = 3.718, P < 0.001), a higher per capita income (t = 6.172, P < 0.001), a higher population density (t = 6.172, P < 0.001), or a lower percentage of elderly population (t = −2.506, P = 0.014) was more likely to have a higher number of dentists per 100,000 population. A municipality that reported a higher Herfindahl-Hirschman Index (HHI) value (t = 2.880, P = 0.005) was more likely to show a higher move-out rate among dentists. The rate was lower after the implementation of the global budget system (t = −2.436, P = 0.018). A municipality that had a higher percentage of elderly population (t = 3.628, P < 0.001), a lower percentage of young population (t = −2.138, P = 0.035), or a higher rate of population growth (t = 4.412, P < 0.001) was more likely to display a higher move-in rate among dentists. The percentage of amalgam restorations in total claims reduced from 19.82% to 17.94%, while the percentage of tooth-colored material restorations increased from 25.46% to 28.79%. Conclusion: This study has demonstrated a stabilizing effect of the global budget system on dynamics of dental manpower in Taiwan. A relationship between HHI and dentists' move-out rate has been found. The relationship between municipal socioeconomic status and the density of dentists has also been confirmed. In addition, reduced utilization of amalgam restorations was accompanied by increased utilization of tooth-colored material restorations. Further investigations are indicated.